Efektivitas Penggunaan Media Pembelajaran Treasure Hunt guna Meningkatkan Keterampilan Berbicara Arab Peserta Didik - Auliannisa, Tazqia; Nursyamsiah, Nunung; Sopian, Asep (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2022)
This study aims to determine the effect and effectiveness of treasure hunt learning media on learning achievement speaking skills. A quantitative approach is used with a Quasi-Experimental design. The population used was the 4th-grade students of SD El Fitra, totaling 111 people. While the sample used is class A as the control class and class B as the experimental class. Analysis of the research data used the t-test which was processed with the help of SPSS version 28 software with the acquisition of sig. (2-tailed) <. 001 in the experimental class <0. 05. So it can be concluded that there is a significant influence on class B who applies Treasure Hunt on learning achievement, especially on the speaking ability of class IV SD El Fitra students.